2012
DOI: 10.1007/s10560-012-0259-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of the Trauma-Informed System Change Instrument: Factorial Validity and Implications for Use

Abstract: In this paper, we present the process of developing and evaluating an instrument designed to measure the extent to which a complex community system has changed as a result of a community initiative, and for purposes of this research, doing this within the content area of developing local trauma-informed child welfare systems in specific communities in Michigan. The instrument was designed for the Southwest Michigan Children's Trauma Assessment Center's (CTAC) Substance Abuse and Mental Health Services Administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…Results from t tests examining changes in individual practices and agency policy and practices on the TISCI (Richardson et al, 2012) showed significant improvements at both the clinician and the agency levels. Mean scores for individual practices were higher at follow-up ( M = 13.50, SD = 0.97) compared to baseline ( M = 11.46, SD = 2.04), t (16) = 5.95, p = .001, as were mean scores for agency practices, M = 86.82, SD = 16.97 compared to M = 80.17, SD = 15.53, t (16) = 3.07, p = .007.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from t tests examining changes in individual practices and agency policy and practices on the TISCI (Richardson et al, 2012) showed significant improvements at both the clinician and the agency levels. Mean scores for individual practices were higher at follow-up ( M = 13.50, SD = 0.97) compared to baseline ( M = 11.46, SD = 2.04), t (16) = 5.95, p = .001, as were mean scores for agency practices, M = 86.82, SD = 16.97 compared to M = 80.17, SD = 15.53, t (16) = 3.07, p = .007.…”
Section: Resultsmentioning
confidence: 99%
“…Individual practice assesses the extent that individuals practice consistently in a trauma-informed manner. The TISCI's internal consistency is adequate (Cronbach's a 录 .53; Richardson et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, trauma-informed practice, in the context of juvenile justice, proffers objective consideration of a child's social, emotional, and developmental life-course in formulating appropriate adjudication and sentencing guidelines. Unlike traditional legal models which are often highly punitive, trauma-informed practice seeks to encourage recognition of the role trauma plays in shaping child behavior, whilst prioritizing approaches most likely to attenuate and help mend the underlying processes that have led to the maladaptive or criminal behavior (Henry et al 2011;Richardson et al 2012).…”
Section: The Implementation Of Trauma-informed Practicementioning
confidence: 99%
“…Still, the perceptions and educational experiences of youth living in residential care remains unchartered territory, and can be useful in understanding how to address the challenges faced by traumatized students in the classroom. Indeed, adults who lack trauma-informed knowledge can easily misinterpret the experiences of traumatized youth and its impact on behavior (Richardson et al, 2012). School personnel may incorrectly assume that youth trauma responses are an indicator of other mental health disorders (Cook et al, 2005; Massachusetts Advocates for Children, 2005), as symptoms of both often appear similar (Griffin et al, 2011).…”
Section: Importance Of Youth Voicementioning
confidence: 99%